The Recovery of Two Polluted Subarctic Lakes—Towards Nutrient Management or a Pristine State? - Erik Grönlund (Water, 2012)
Two small subarctic lakes were eutrophicated due to wastewater discharge from 1964. In 1975, a wastewater treatment plant was built and a recovery process started. This paper will: (1) compile the 1972–1974, 1978–1980 and 1985–1988 investigation data regarding phosphorous and microalgae for one of the lakes; (2) complement with unpublished data from 1985 and 2003; and (3) introduce a discussion regarding three alternatives for future development of the lakes in their last phase of recovery. In the latest investigation, 2003, the lakes were assessed as almost recovered. They had returned to an oligotrophic state, but not fully to a pre-sewage situation. In the upper lake, more heavily polluted, the total phosphorous levels had decreased from an average of 168 µg P/L in 1972–1974 to an average of 12 µg P/L in 2003. The phytoplankton biomass had decreased twentyfold during the same period, from 11.2 mg/L to 0.6 mg/L. The Secchi depth had increased from 1.3 m to 2.8 m. The low oxygen level in late winter was still not recovered, thereby profoundly affecting residential organisms in the lakes. The low winter oxygen is assumed to remain so for a long time due to phosphorus release from sediments in the lakes.